Analysis of land carrying capacity and production factors of cocoa (Theobroma cacao L.) in Banggai Regency - Krisniati Pamanyo; Dian Puspapratiwi; Hertasning Yatim; Hidayat Arismunandar Katili; Mihwan Sataral; Taufik Bidullah (Jurnal Ilmiah Pertanian, 2021)
This study aimed to determine the carrying capacity of land and production factors in the development of cocoa production in the Banggai Regency of Central Sulawesi. This research was conducted in 23 sub-districts of the Banggai Regency. Determination of respondents using cluster sampling method or grouping based on area or population location with 114 cocoa farmers. The research data were obtained from primary data, i.e., interviews, questionnaires. In contrast, secondary data were obtained from the Central Statistics Agency, the Banggai Regency Agriculture Office, and the Center for Research and Development on Agricultural Land Resources. The variables analyzed include regional economics (used LQ and SSA), land carrying capacity (DDL), and the production factors were land area (X1), number of workers (X2), fertilizer costs (X3), and pesticide costs (X4). Thus, this study indicated the direction of land allocation based on the regional economy, land carrying capacity, and cocoa production factors. Overall, cocoa plants could be developed in the Banggai Regency with an area of 419,236.9 hectares. However, there was a need for sound land use data management and intensive cocoa cultivation assistance to increase comparative and competitive human resources and improve the economy for the welfare of the cocoa farming community in the Banggai Regency.